Contribution towards the development of a management plan for the baitboat and sport fishery for tuna in South Africa - Newcombe, Hylton Cecil (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2012)
Tuna are of significant global economic importance and a prime food source. Increased levels of fishing have resulted in many stocks being under threat and a number of species are considered to be overfished. The South African tuna industry has had limited management attention from the South African fisheries management agency. A recent development has been an increase in the number of tuna caught by small vessels that target the fresh tuna market in South Africa and overseas. This has highlighted the importance of developing a holistic management plan for the sector and creating an awareness, among vessel owners, of the importance of compliance with initiatives such as the Marine Stewardship Council (MSC). The South African tuna fishery comprises three sectors: baitboat, sport and longline, all of which are currently in need of acquiring more biological and fisheries data. This project was initiated to collate existing information and to collect additional information where possible. This encompassed a qualitative and quantitative assessment of the size and shape of the tuna fishing industry, which included estimates of total catch, effort, catch-per-unit-of-effort (CPUE) and stock structure (obtained through comparative estimates of age and growth), as well as socio-economic and economic information. A technique involving an examination of specific vertebrae was used to obtain age-growth information for T. albacares. These data were used to estimate von Bertalanffy (VBGF) growth parameters: F 2 1. , k 0.1 , and tâ‚€ -0. 1 year. No significant differences in growth parameters were found in yellowfin tuna (Thunnus albacares) from different localities around the South African coast, i.e. from the south eastern Atlantic and the south western Indian Ocean. In addition, growth did not differ between South Africa and other regions (Draganic and Pelzcarski 1984, Fonteneau 1980, Gascuel et al. 1992, LeGuen and Sakagawa 1973, Lehodey and Leroy 1999, Lessa and Duarte-Neto 2004, Shuford et al. 2007, Stequert et al. 1996, Wild 1986, Yang et al. 1969). Further substantiation of the above-mentioned observations was found by recording differences in the sizes of fish caught in the inshore (baitboat and sport fishery vessels) and offshore (large pelagic longline vessels) sectors of South African tuna fisheries. A significant difference between the regions "” in terms of the size of fish caught inshore "” was noted, with mostly-juvenile fish being caught in KwaZulu-Natal (5.4 Â± 3.5kg), sub-adult fish in the Eastern Cape (26.2 Â± 13.4kg), and adult fish in the Western Cape (42.3 Â± 14.4kg). Since mostly-adult fish were caught offshore by longliners, with no significant differences between regions, it is however possible th at adult fish predominantly inhabit the offshore region. Yellowfin tuna caught by the large pelagic longline fishery in the three managerial zones (A, B and C) were predominantly adult fish of similar size, namely Zone A: 38.9 Â± 6.9kg; Zone B: 28.7 Â± 4.6kg, and Zone C: 36.0 Â± 5.1kg. The recreational ski boat sport fishery has remained stable, in terms of participation, consisting mostly of white middle aged males in the top 25% of household income distribution, having either permanent occupational status or being retired. Fishers within this sector are willing to incur great expense to partake in the fishery and they provide an important economic contribution to coastal towns, particularly in the Eastern Cape. The total catch (of 83t) of yellowfin tuna by the competitive sport fishery within the Western and Eastern Cape regions was considerably lower than that of commercial tuna baitboat catches, which amounted to 186t, and the large pelagic longline sector that caught t in 200. It is however likely that the competitive sport fishery's total yellowfin tuna catch (of 83t in 2009) of the Eastern and Western Cape competitive sport fishery was considerably less than the total yellowfin tuna catches of the whole South African deep-sea sport fishery. Longfin tuna are the primary target species of South Africa's baitboat fisheries, comprising an average of 86% of the total catch and generating ZAR49 million in employment income in 2002. South Africa was responsible for 20% of the total longfin tuna annual yield in 2004 in the southern Atlantic Ocean, behind Taiwan with 59%. However, yellowfin tuna only contributes a small percentage towards total catches (8.4 Â± 8.2% between 1995 and 2009), generating ZAR1.3 million in employment income in 2002. Of the four vessel categories comprising the tuna baitboat fishery, ski boats had the highest yellowfin tuna CPUE in 2009 (117 Â± 62 kg.vesselâ »Â¹.dayâ »Â¹) and the lowest effort. The ski boats sector is the most opportunistic fishery as they are only active when either longfin or yellowfin tuna are in high abundance. At such times catches are guaranteed, so can be expected to offset expenses. In 2009 the CPUE for yellowfin tuna for 15"“19m vessels and freezer deckboats was 12 Â± 20kg.vesselâ »Â¹.dayâ »Â¹ and 3 Â± 6kg.vesselâ »Â¹.dayâ »Â¹, respectively. These vessels specifically target longfin tuna when they are in abundance. Since the start of the tuna baitboat fishery in 1995, there has been a substantial increase in the number of new entrants. In 2002 this sector had a fleet size of 82 vessels with a capital value of ZAR163 million and a total employment income of ZAR58 million, employing 2 173 fishers, of which 87% were black African. The commercial tuna baitboat fleet has subsequently grown to 200 vessels and 3600 crew, with 110 active vessels fishing for a combined fleet average of 46 days per year. There are a high number of owner-operated vessels. Since 2007 the fishery's profit to cost ratio has been low due to the low abundance of tuna stocks off the coast of South Africa, which has resulted in poor catch returns, placing economic pressure on the fishery. The baitboat industry is a low-profit-margin fishery with a total net catch value worth ZAR90 million in 2009 (Feike 2010). The abundance of yellowfin tuna influences profit margins, with very high profits being made when abundance and catches are high. The large pelagic longline fishery has a total allowable effort of 43 vessels of which only 30 vessels fished during 2009, when a reported 766t of yellowfin tuna were caught, representing a total tonnage far in excess of that obtained by the combined effort of the baitboat and sport fishery. It is, however, assumed that considerable underreporting of catches takes place within this fishery, which means that the estimated total net catch value of ZAR100 million could, in fact, be much higher. Such underreporting of catches is of great concern for this fishery, as is the high bycatch of Chondricthians spp. that significantly outweighs imposed regulatory limits (DEAT 2007). The present study demonstrates the current lack of comprehensive catch and effort data for the sport, baitboat and longline fisheries as well as the serious limitations and flaws associated with current databases. Results from the present study have drawn attention to a number of high-priority research needs, as outlined below. (1) A major lack of comprehensive catch and effort data for the sport fishery, which can be rectified by focussing on obtaining more competition data, as well as high-quality catch and effort and socio-economic information, as opposed to relying on information from non-club anglers (Gartside et al. 1999, Williams 2003, Cass-Calay 2008). Acquisition of such data is relatively inexpensive: the location of organized clubs and their frequent competition meetings provide widespread coverage along the Southern African coastline. Such data acquisition efforts have the potential to provide reliable information on spatial catch trends. (2) Validation of vessel catch return data is required for commercial fisheries and on some recent data that has emerged from studies of catch rates and trends for target species, particularly in the longline fishery. In this context it should be noted that the most recent peer-reviewed publications on this exploratory fishery were published more than a decade ago (Kroese 1999, Penny and Griffiths 1999). Additional studies need to be undertaken and journal articles published on the current stock status of South African catches of yellowfin and bigeye tuna and swordfish.
Keywords: Tuna -- South Africa; Tuna fishing -- South Africa; Fishery management -- South Africa; Fishery management -- Economic aspects -- South Africa; Tuna fisheries -- Catch effort -- South Africa; Tuna fisheries -- Economic aspects -- South Africa